2022
DOI: 10.1039/d2ra07080d
|View full text |Cite
|
Sign up to set email alerts
|

The importance of tetrel bonding interactions with carbon in two arrestive iso-structural Cd(ii)–Salen coordination complexes: a comprehensive DFT overview in crystal engineering

Abstract: Two preeminent iso-structural Cd(ii)–Salen complexes were synthesized and structurally characterized. The unique tetrel bonding interactions involving the CH3 group have been reported in a reassessed dimension of the DFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The ligand’s spectrum was taken in methanol, while the complex was tested in DMF solvent (Figure S3). Based on the spectral results, we found that the ligand had peaks at 283 and 334 nm, while the complex had significant peaks at 278 and 321 nm . According to the findings, two electronic transitions arise from the ligand and the complex.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The ligand’s spectrum was taken in methanol, while the complex was tested in DMF solvent (Figure S3). Based on the spectral results, we found that the ligand had peaks at 283 and 334 nm, while the complex had significant peaks at 278 and 321 nm . According to the findings, two electronic transitions arise from the ligand and the complex.…”
Section: Resultsmentioning
confidence: 82%
“… ,, The azomethine linkage in the complex was identified at 1620 cm –1 compared to the salen ligand at 1631 cm –1 (Figure S1,S1A). Notably, the IR spectra of the OCN – ions in standard KOCN salts show strong bands near 2176 cm –1 (Figure S1B), while in the zinc metal complex with O-coordinated stretching of OCN – ions were observed at 2182 cm –1 (Figure S1A). The comparative IR spectral approach helps to determine whether or not OCN – can link with zinc metal ions and that this linking occurs through an O-atom.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiocyanate-related complexes exhibit diverse binding chemistry and form versatile structural bridging motifs with metal ions. Coordination polymers, especially those with SCN − -ligands, are notable in coordination chemistry for their intriguing architectural frameworks and diverse bonding functionalities seen in X-ray crystal structures [ [22] , [23] , [24] , [25] ]. Analyzing coordination polymer analogs through crystallography helps researchers understand their structural relationships, similarities, and differences, aiding in exploring their properties and applications.…”
Section: Introductionmentioning
confidence: 99%
“…Non-covalent interactions are potent tools for crystal engineering and supramolecular building architectures of coordination compounds that may be discrete or polymeric . Here, crystal structure analysis breaks down the complex’s minute structural features, while further quantifying the intermolecular interactions through Hirshfeld surface analysis and density functional theory (DFT) analysis. …”
Section: Introductionmentioning
confidence: 99%